Perspektivisk Textanalys (PTA): Manual till Vertex med danskt material - Bierschenk, Inger; Bierschenk, Bernhard (Kognitionsvetenskaplig forskning : Cognitive Science Research, 2013)
The present work is based on the Kantian (AaO)-axiom and conceptualised as textbook. As scientific method in the true sense of the notion science, the Vertex version of Perspective Text Analysis represents a completely new approach to text-based studies. The core of Vertex is introduced by means of instructions to a stepwise procedure. The steps are richly illustrated. The inter-lingual character of Vertex has been tested and established in the context of six different languages, four belonging to the German family and two to the Roman family. The instructions are in Swedish, but text data are Danish and because of this an introductory part in Danish has been provided. To profit as much as possible from the configuration of exercises, the approach to the text example is designed for step-by-step processing. Against this background, it is possible to bring out a number of principles for process-oriented procedures. Of particular significance is the endeavor to build up an understanding of the import of objective text processing. This means that the single steps should be carried out in a way that circumvents that one’s own imaginations and prejudices about the content of a text enter into the analysis.
Keywords: potential energy surfaces; magnitudes; fusion dynamics; flow dynamics; language space; Kantian AaO-axiom; functional text geometry; perspective text analysis (PTA); free energy surfaces; energy landscapes; Danish